2005
DOI: 10.1172/jci26169
|View full text |Cite
|
Sign up to set email alerts
|

SOCS1 restricts dendritic cells' ability to break self tolerance and induce antitumor immunity by regulating IL-12 production and signaling

Abstract: DC-based tumor vaccine research has largely focused on enhancing DC maturation/costimulation and antigen presentation in order to break tolerance against self tumor-associated antigens. DC immunization can activate autoreactive T cells but rarely causes autoimmune pathologies, indicating that self tolerance at the host level is still maintained in the vaccinated hosts. This study in mice reveals a novel regulatory mechanism for the control of self tolerance at the host level by DCs through the restriction of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 52 publications
10
126
0
Order By: Relevance
“…In a study of an animal model of melanoma, continuous TLR2, 3, 4, or 7 stimulation elicits cytotoxic T-cell generation, but no in vivo effect on anti-tumor responses reflected by uninterrupted tumor growth and no signs of autoimmunity (vitiligo) in treated animals can be observed. Additional modification of the TLR signaling pathway including SOCS1 inhibition in DCs induces effective anti-melanoma immunity with marked IL-12 secretion and visible tumor growth suppression [104]. Moreover, genetic immunization along with TLR ligation is not efficient enough in the treatment of melanoma in mice, suggesting the existence of active tumor immunotolerance.…”
Section: The Results Of Tlr Activation -Tlrs In Carcinogenesismentioning
confidence: 99%
“…In a study of an animal model of melanoma, continuous TLR2, 3, 4, or 7 stimulation elicits cytotoxic T-cell generation, but no in vivo effect on anti-tumor responses reflected by uninterrupted tumor growth and no signs of autoimmunity (vitiligo) in treated animals can be observed. Additional modification of the TLR signaling pathway including SOCS1 inhibition in DCs induces effective anti-melanoma immunity with marked IL-12 secretion and visible tumor growth suppression [104]. Moreover, genetic immunization along with TLR ligation is not efficient enough in the treatment of melanoma in mice, suggesting the existence of active tumor immunotolerance.…”
Section: The Results Of Tlr Activation -Tlrs In Carcinogenesismentioning
confidence: 99%
“…Some of the well-recognized tumor immune evasion mechanisms include failure of tumor antigen recognition (4-6), modulation of MHC molecule expression (7,8), improper activation of antigen-presenting cells (APC; refs. 1, 9), failure of lymphocyte homing (1,10), and production of immunosuppressive cytokines (11,12). These immunologic abnormalities associated with the tumor microenvironment either inhibit the priming of antitumor adaptive immunity (1) or tolerize tumor-specific CD4 (13,14) and CD8 (15,16) T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that IL-12 signaling is enhanced when SOCS1 is downregulated in T cells and DCs [17,35]. IL-12 is required for induction but not maintenance of memory T1 (type 1 T cell) responses [24].…”
Section: Discussionmentioning
confidence: 99%
“…The suppressor of cytokine signaling 1 molecule (SOCS1) controls signaling of many cytokines, including IFN-γ, IFN-α, IL-2, IL-4, IL-6, IL-7, IL-10, IL-12, IL-15, and IL-21 utilizing a feedback loop mechanism [10][11][12][13][14][15][16][17][18][19]. First, binding of a cytokine to its receptor upregulates expression of SOCS1.…”
Section: Introductionmentioning
confidence: 99%